Materials and technology a systematic encyclopedia of the technology of materials used in industry and comerce, including foodstuffs and fuels based upon a work originally devised by the late Dr. J.F. van Oss : petrolium and organic chemicals (Longmans J.H. Debussy, 1968)
xxxi, 792 p.; 25 cm.